Review of 1971/02/05 Concert at Barber Institute of Fine Arts, University of Birmingham. Contemporary music concert of works by Goehr, Stravinsky, Debussy, Connolly, Boulez and Revel, given by members of the Nash Ensemble - Fairhurst, Peter (Contact: A Journal for Contemporary Music (1971-1990), 1971)